Matrix Metalloproteinase-9 Level and Gene Polymorphism in Sleep Disordered Breathing Patients with or without Cardiovascular Disorders - VELİOĞLU ÖĞÜNÇ, AYLİZ; YÜKSEL, MERAL (AVES YAYINCILIK, 2013)
Objective: Obstructive sleep apnea syndrome (OSAS) is associated with increased cardiovascular morbidity and mortality. We aimed to investigate the matrix metalloproteinase-9 (MMP-9) level and MMP-9 gene polymorphism in sleep apnea patients with or without cardiovascular disease. Study Design: Case-control study. Material and Methods: Two hundred nine patients [Mean age (+/- SD), 47 (+/- 12) yrs; M/F, 170/39] diagnosed with sleep-disordered breathing were included in the study. Serum MMP-9 level was performed using enzyme-linked immunosorbant assay (ELISA) and MMP-9 gene polymorphism with polymerase chain reaction-restriction fragment length polymorphism. We divided the patient group into two subgroups: (1) patients with confirmed cardiovascular disease, i.e. CV-P Group and (2) patients without cardiovascular disease, CV-N Group. We compared all parameters between the two groups. Results: There were 56 OSAS patients with cardiovascular disorder (CV-positive group) and 153 OSAS patients without cardiovascular disorder (CV-negative group). CC, CT and TT genotype distributions between groups were similar [31 (55%), 25 (45%), 0 (0%) vs 88 (57%), 61 (40%), 4 (3%); respectively, p>0.05]. MMP-9 level was significantly higher in CV-P patients (442.7 +/- 139.3 pg/mL) than in CV-N patients (364.4 +/- 165.0 pg/mL; p=0.0018). Conclusion: Our results showed that the presence of MMP-9 polymorphism was not associated with cardiovascular disease. MMP-9 level was higher in OSAS patients with cardiovascular disorders than without cardiovascular disorders. Finally, MMP-9 genotype was not associated with serum MMP-9 levels.
Keywords: Cardiovascular disease; MMP-9; polymorphism; sleep apnea; hypertension; CORONARY-ARTERY-DISEASE; FUNCTIONAL POLYMORPHISM; APNEA SYNDROME; GELATINASE; EXPRESSION; RISK